The Influence Of Work Motivation, Leadership, And Organizational Culture On Employee Performance At PT Pelindo Multi Terminal - Jiehan Ukhti Harissa; Teguh Wahyono; Soulthan Saladin Batubara (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This research aims to analyze the influence of work motivation, leadership, and organizational culture on employee performance at PT Pelindo Multi Terminal Branch Belawan. Employee performance is an important aspect in achieving company goals, which can be influenced by the level of motivation, leadership style, and work culture applied. The method used is a quantitative approach with a survey technique, involving 98 respondents who are permanent employees. Data was obtained through the distribution of questionnaires and analyzed using multiple linear regression. The results showed that work motivation, leadership, and organizational culture simultaneously have a significant influence on employee performance. Partially, these three variables also provide a positive and significant influence. Work motivation: t-count value of 1.410 < t-table 1.661 (n–k = 98–4 = 95, α = 0.05) with a significance of 0.002 < 0.05. This indicates that motivation has a positive and significant effect on employee performance, so Ha is accepted and Ho is rejected. Leadership: t-count value 9.214 > 1.661 with a significance of 0.000 < 0.05. This means that leadership has a positive and significant effect on employee performance. Organizational culture: t-count value 3.519 > 1.661 with a significance of 0.001 < 0.05. This proves that organizational culture also has a positive and significant effect on employee performance.